Foreign exchange and the capital market dynamics: New evidence from non-linear autoregressive distributed lag model - Osaretin Kayode Omoregie; Sodik Adejonwo Olofin; Fredrick Ikpesu (International Journal of Management, Economics and Social Sciences (IJMESS), 2020)
The purpose of this study was to investigate and analyze the relationship between foreign exchange and capital market dynamics in Nigeria from January 1999 to February 2018. The study deployed the Non-Linear-ARDL model to study the dynamics of exchange rate and the capital market in Nigeria. The research outcome revealed that a rise (fall) in all-share-index is related to real exchange rate depreciation (appreciation), while real exchange rate depreciation (appreciation) is associated with an increase (decrease) in all-share-index. Besides, the research outcome also showed that there is a presence of time-specific long-run, bi-directional, and unidirectional causality with stronger interrelation after the Global Financial Crisis. The study recommends that to properly hedge and diversify portfolio against potential risk in these two markets, market players need to understand the dynamics between them.
Keywords: C1; C5; G1; G15; 330; Real exchange rate; capital market; stock-index; NARDL; causality